2021
DOI: 10.1371/journal.pone.0260786
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular dynamic binary complexes with pH and salt-responsive properties for use in unconventional reservoirs

Abstract: Hydraulic fracturing of unconventional reservoirs has seen a boom in the last century, as a means to fulfill the growing energy demand in the world. The fracturing fluid used in the process plays a substantial role in determining the results. Hence, several research and development efforts have been geared towards developing more sustainable, efficient, and improved fracturing fluids. Herein, we present a dynamic binary complex (DBC) solution, with potential to be useful in the hydraulic fracturing domain. It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 73 publications
0
4
0
Order By: Relevance
“…The overall procedure in place for the rheological studies is comparable to that of previous studies. 18,35,36 Viscosity versus shear rate was measured in each case using a rheometer (Haake RS 1, Thermo Fisher Scientific, Waltham, MA, USA) equipped with a 60 mm diameter parallel plate (PP60 Ti). The shear rate was increased logarithmically and stepwise (15 steps) from 0.003 s À1 to 100 s À1 , while setting the gap between the plates constant at 1 mm.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…The overall procedure in place for the rheological studies is comparable to that of previous studies. 18,35,36 Viscosity versus shear rate was measured in each case using a rheometer (Haake RS 1, Thermo Fisher Scientific, Waltham, MA, USA) equipped with a 60 mm diameter parallel plate (PP60 Ti). The shear rate was increased logarithmically and stepwise (15 steps) from 0.003 s À1 to 100 s À1 , while setting the gap between the plates constant at 1 mm.…”
Section: Rheological Measurementsmentioning
confidence: 99%
“…Therefore, the development of novel nanostructures of the supramolecular self-assemblies has been widely studied to attain the desired rheological properties. 6 Recently, a complex self-assembly called the dynamic binary complex (DBC) has been synthesized by Liu et al 7 via the complexation between zwitterionic amphiphiles like octadecylamidopropyl betaine (OAPB) and diethylenetriamine (DTA) ions. Specifically, DBCs have unique viscoelastic properties which show sensitivity to the solution conditions like pH.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, DBCs have unique viscoelastic properties which show sensitivity to the solution conditions like pH. In recent studies, 6,7 it was observed that DBCs consist of tubular nanostructures, and the viscoelastic properties of DBCs are determined by the entanglement process of these tubular nanostructures whose cross-sectional dimensions are almost an order of magnitude larger than those of the conventional tubular wormlike micelles (WLMs). It is difficult to rely on the existing imaging techniques like transmission electron microscopy (TEM) to image microgels such as DBCs.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation